A Review of Face and Speech multimodal Biometrics for security using Genetic Algorithm - Bansal, Nancy; Singh, Samanpreet (International Journal of Computer Sciences and Engineering, 2025)
Multimodal biometrics is the combination of two or more modalities such as face and speech modalities. In two modalities have been presented with genetic algorithm to show the effect of Genetic algorithm in the accuracy level of a biometric system. Face recognition is the most popular physiological characteristic used to identify a person in biometric systems, because of feasibility, permanence, distinctiveness, reliability, accuracy, and acceptability. On the other hand speech recognition is the most popular behavioral characteristic used in biometric systems. Thus, we believe that the combination of these two methods will have reliable and accurate results. So, this paper has provided the review using an evolutionary method.